Blender 2.5 character animation cookbook : 50 great recipes for giving soul to your characters by building high-quality rigs and understanding the principles of movement - Vasconcelos, Virgilio (Packt Pub., 2011)
Part of Packt's Cookbook series, each chapter focuses on a different aspect of animation. If you don't have the time to work your way through a long tutorial, then this is the book for you. The step-by-step recipes are independent from each other so you can dip in and out of the book to add great effects as and when you need them. Blender users who already know the basics of adding, modeling and rendering objects within the program, but are eager to learn how to turn a character's mesh into a living creature.